2019
DOI: 10.30997/jsei.v4i2.1486
|View full text |Cite
|
Sign up to set email alerts
|

Strategy of Optimalization Cash Waqf in Indonesia

Abstract: This study aims to identify various problems of cash waqf management in Indonesia. Identification of these various problems is expected to be formulated by various alternative solutions. Based on the research, it was identified that there were three main obstacles in the process of optimizing cash waqf, namely socialization, regulations and Nazhir, all of which were broken down in several sub-problems. The solutions that can be offered from these three constraints are socialization programs, both on understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
(3 reference statements)
0
3
0
1
Order By: Relevance
“…Menurut hasil penelitian Nadya et al (2018), ada tiga poin penting dalam kendala optimalisasi wakaf uang di Indonesia yaitu sosialisasi, regulasi dan profesionalisme nazir. Dalam upaya sosialisasi wakaf uang juga terdapat beberapa kendala, seperti kurangnya pemahaman publik mengenai wakaf uang, persepsi masyarakat tentang wakaf uang, dan ketidakpercayaan publik terhadap mekanismenya.…”
unclassified
“…Menurut hasil penelitian Nadya et al (2018), ada tiga poin penting dalam kendala optimalisasi wakaf uang di Indonesia yaitu sosialisasi, regulasi dan profesionalisme nazir. Dalam upaya sosialisasi wakaf uang juga terdapat beberapa kendala, seperti kurangnya pemahaman publik mengenai wakaf uang, persepsi masyarakat tentang wakaf uang, dan ketidakpercayaan publik terhadap mekanismenya.…”
unclassified
“…The low realization of sales result of SWR001 led to the threat of many social programs that had been planned by nadzir not being implemented properly. It is necessary to carry out a comprehensive evaluation of the stakeholders so that the existing potential can be utilized optimally (Nadya et al, 2018). Several strategies that can be taken to market the next series of retail waqf sukuk include offering to existing wakif that have been registered at Islamic Financial Institutions Receiving Cash Waqf (LKS-PWU), offering priority customers, holding more massive socialization, and cross selling to customers individuals and institutions (Tanjung, 2020).…”
Section: Future Direction Of Cash Waqf Linked Sukukmentioning
confidence: 99%
“…As hundreds of studies they confirmed that Waqf is an efficient method to alleviate poverty. On the other hand, the contemporary scholars are focusing on maximizing the benefits of cash waqf, for example Nadya, Alwyni, Hadiyati, & Iqbal (2019); while others concentrate on the Waqf manager accountability (Siswantoro et al, 2018).…”
Section: Previous Studiesmentioning
confidence: 99%
“…After the announcement of both Malaysian and Indonesian government, many Waqf institutions have been established (Nahar and Yaacob, 2011). Nadya et al (2019) indicated that cash Waqf in Indonesia facing three main difficulties to reach its optimal level, regulations, Nazhir, and socialization. Another study addressed the Indonesian context by Nahar and Yaacob (2011) established that the Indonesian Awqaf institutions have a unique characteristic.…”
Section: Management Of the Cash Waqfmentioning
confidence: 99%